MINAT DAN STRATEGI BERWIRAUSAHA (Studi Analisis Pada Mahasiswa STEI LPPM Padalarang Bandung Barat) - Maryati (Jurnal Pelita Nusa, 2021)
ABSTRACT This study aims to (1) determine the entrepreneurial interest of STEI LPPM Padalarang Bandung Barat students, (2) determine the factors that influence the entrepreneurial interest of STEI LPPM Padalarang Bandung Barat students and (3) determine strategies that can be applied in fostering entrepreneurial interest in STEI LPPM students. Padalarang West Bandung. The results showed that as much as 2% of STEI LPPM Padalarang West Bandung students have carried out entrepreneurial activities in addition to carrying out their main duties as students. The test results collectively show that the variable desire for high-income expectations, support from family, and education affects students' interest in entrepreneurship. Keywords: Interests, Strategies, Entrepreneurship